Genetic evaluation and characterization of jute (Corchorus spp. L) genotypes using DUS (SAARC Journal of Agriculture, 2014)
In this study 32 jute (Corchorus spp.) varieties comprised of 18 olitorius and 14 capsularis were evaluated and characterized for five quantitative and 12 qualitative characters as per revised official DUS Test Guidelines of Jute. The experimental materials were grown in a RBD with three replications at Baarrackpore, India during 2009-10. Significant differences among genotypes noted almost for almost all the quantitative traits. PCV and GCV were highest for 1000 seed weight (33.78 and 33.29%) followed by fibre fineness (27.11 and 26.70%). Low variability was recorded in case of plant height. All the five characters exhibited more or less high heritability coupled with high genetic advance as per cent over mean. Out of 12 qualitative characters studied, in C. capsularis 8 traits were monomorphic, 4 traits were dimorphic. However, in C. olitorius no trait was monomorphic, 6 traits were dimorphic and 6 traits were polymorphic among varieties indicating their potential for varietal characterization. DOI: http://dx.doi.org/10.3329/sja.v10i2.18335 SAARC J. Agri., 10(2): 147-153 (2012)